2019
DOI: 10.1155/2019/1093815
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Pathological Mechanism of Bladder Cancer Based on Tumor Mutational Burden Analysis

Abstract: Although immunotherapy has progressed in the treatment of bladder cancer, some patients still have poor prognosis. New therapeutic targets are eager to be discovered to improve the outcomes of bladder cancer. With the development of high-throughput sequencing and tumor profiling, potential tumor biomarkers were identified. Through the interpretation of related data from the Cancer Genome Atlas database (TCGA), some key genes have been discovered to drive the development and prognosis of urinary bladder neoplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…Immune checkpoint molecule inhibitors have opened the possibility of immunotherapy for bladder cancer, especially for muscle-invasive and metastatic bladder cancer [24,25]. Recent research has correlated bladder cancer and the immune environment [26]. However, there are no available biomarkers to assess the effectiveness of immunotherapy in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Immune checkpoint molecule inhibitors have opened the possibility of immunotherapy for bladder cancer, especially for muscle-invasive and metastatic bladder cancer [24,25]. Recent research has correlated bladder cancer and the immune environment [26]. However, there are no available biomarkers to assess the effectiveness of immunotherapy in bladder cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Neoantigens are associated with tumor mutational burden (TMB) 17 ; patients with higher TMB can potentially form more neoantigens, thereby promoting anti‐tumor immune responses 18 . TMB has been used to predict the efficacy of immune checkpoint inhibitors (ICIs) in various cancers, including TNBC 19–24 . In addition, previous studies have demonstrated that combination of TMB and immune gene expression profile (GEP) could further distinguish responders from non‐responders in TNBC patients treated with ICIs 25 .…”
Section: Introductionmentioning
confidence: 99%
“…The somatic mutation accumulation promotes the formation of neoantigens which activate the immunogenicity of T cells to kill cancer cells. The cancers with high TMB often generate new antigens to recruit the immune cells ( 35 ). Consistent with the previous studies, our results showed that higher TMB tends to predict worse survival.…”
Section: Discussionmentioning
confidence: 99%